Effect of catheter design on tracheal pressures during tracheal gas insufflation. - John Dingley (Eur J Anaesthesiol, 2003)
BACKGROUND AND OBJECTIVE:This study investigated the distribution of pressures within a model trachea, produced by five different tracheal gas insufflation devices. The aim was to suggest a suitable design of a tracheal gas insufflation device for clinical use.METHODS:Each device was tested using insufflation flow rates of 5 and 10 L min(-1). For each flow rate, the pressure within the tracheal model was measured at 33 fixed points.RESULTS:The Boussignac tracheal tube produced the most even pressure distribution, while a reverse-flow catheter produced pressure changes of the smallest magnitude.CONCLUSIONS:We suggest that catheters producing the lowest pressure changes are likely to be safer for clinical use.